TECHNOPOLITICS IN URBAN REGENERATION CO-CREATING PUBLIC SPACE CONFERENCE PROCEEDINGS - Paio, A.; Cardoso, A.; Farias, A. C. C.; Graça, A.; Pomesano, L. (2019)
In twenty-first century, urbanization and ecosystems deterioration are affecting cities and their peripheries making them the nexus of mankind’s challenges and opportunities. Conventional top-down master planning and municipality policymaking are not delivering the systemic changes needed to improve urban space living conditions for city citizens. International Conference and Summer School’2019 Technopolitics in Urban Regeneration: Co-creating Public Spaces will tackle several questions with an argument that cities are a melting pot of new forms of sociability and collective action founded on an association between humans and digital technologies. The democratization of technology and its ever-increasing influence in our everyday life have amplified new ways in which citizens can access information and make decisions of all kinds. Anyone, anywhere, can design, share, download, adapt and digitally print products. Digital participatory platforms are blurring the boundary lines between short-time design and long-term planning. Geolocation technologies and real-time automated data capture are changing the models of participation and design. In addition, for a space to be authentically public, it must be open, democratic and engageable. Users of public spaces should have the opportunity to activate themselves as agents of change in the contemporary city. All over the world, community-based initiatives indicate the ability of city citizens to present solutions. In this context, is fundamental to discuss the progressive emergence of spatialised intelligence. Digital participatory methods have been developed and experimented in public space design, giving birth to a wide set of opportunities and challenges in cross-disciplinary collaboration. So, what is at the current cutting edge of public spaces design? To answer these questions, during two weeks participants will discuss ways to develop urban solutions based on co-creation processes, giving voice to different stakeholders who can play an important role in the rebuilding of public space on a local scale. Co-Creation to be successful it is important to identify networks and involve different types of participants Co-Creation to be successful it is important to identify networks and involve different types of participants that can take advantage of effective collaborative partnership. This event opens up opportunities to share international best practice and research, to pinpoint fields of opportunity for actions, and to highlight their importance to the onstruction of a city. The two days conference aims to contribute to enrich the debate around the use of digital technologies in bottom-up urban public space design strategies. The conference is structured in four thematic sessions: (1) Collaboration in digital condition; (2) Civic laboratories; (3) Community Participation and Toolkits; and (4) Digital Collective Mapping. Each session will start with keynote speaker lecture followed by paper presentations sessions. The design studio takes place in a real scenario in order to integrate technological knowledge with strategic design concerns. The four days master classes are designed to engage all the participants in an integrated collaborative learning approach to develop an urban design solution in Cascais. The scope is to establish inclusive strategies that link students, researchers, citizens, and municipality with different expertise and increase their ability to deal with the Urban Regeneration and Co-creating design methods for Public Spaces.